Occurrence of Fasciola hepatica (Linnaeus, 1758) in capybara (Hydrochoerus hydrochaeris) (Linnaeus, 1766) in Minas Gerais, Brazil - Dracz,Ruth Massote (2016)
Abstract Fasciola hepatica is a parasite that affects the hepatic ducts of several species of domestic and wild vertebrates, causing huge economic losses to livestock rearing worldwide. Reports on occurrences of F. hepatica in capybaras are an important epidemiological aspect of this disease, since these rodents can be a source of contamination for other animals and humans. In the present study, conducted in a rural area of the municipality of Confins, Minas Gerais, fresh feces from capybaras were collected from the ground near a lagoon at the edge of the Ribeirão da Mata river. These were examined using the technique of four metal sieves. F. hepatica eggs were recovered. This trematode species was confirmed by observing morphological characteristics and measuring the eggs recovered from the capybara feces, and through experimental infection of Lymnaea columella (Say, 1817) by miracidia from these eggs and subsequent infection of C57/BL06 mice with metacercariae originating from these infected mollusks. The data suggest the occurrence of natural cycle of F. hepatica in this region and provide a warning that expansion of the geographical distribution of this parasite by means of this rodent is possible. It is therefore important to adopting measures for epidemiological control of this helminthiasis.